Assessing the Relationship between Indexed Epicardial Adipose Tissue Thickness, Oxidative Stress in Adipocytes, and Coronary Artery Disease Complexity in Open-Heart Surgery Patients - Laurentiu Braescu; Adrian Sturza; Oana Maria Aburel; Raluca Sosdean; Danina Muntean; Constantin Tudor Luca; Daniel Miron Brie; Horea Feier; Simina Crisan; Cristian Mornos (Medicina, 2024)
Background and Objectives: This cross-sectional study conducted at the Timișoara Institute of Cardiovascular Diseases, Romania, and the Centre for Translational Research and Systems Medicine from “Victor Babeș” University of Medicine and Pharmacy of Timișoara, Romania, investigated the relationship between indexed epicardial adipose tissue thickness (EATTi) and oxidative stress in epicardial adipose tissue (EAT) adipocytes in the context of coronary artery disease (CAD) among open-heart surgery patients. The objective was to elucidate the contribution of EATTi as an additional marker for complexity prediction in patients with CAD, potentially influencing clinical decision-making in surgical settings. Materials and Methods: The study included 25 patients undergoing cardiac surgery, with a mean age of 65.16 years and a body mass index of 27.61 kg/m2. Oxidative stress in EAT was assessed using the ferrous iron xylenol orange oxidation spectrophotometric assay. The patients were divided into three groups: those with valvular heart disease without CAD, patients with CAD without diabetes mellitus (DM), and patients with both CAD and DM. The CAD complexity was evaluated using the SYNTAX score. Results: The EATTi showed statistically significant elevations in the patients with both CAD and DM (mean 5.27 ± 0.67 mm/m2) compared to the CAD without DM group (mean 3.78 ± 1.05 mm/m2, p = 0.024) and the valvular disease without CAD group (mean 2.67 ± 0.83 mm/m2, p = 0.001). Patients with SYNTAX scores over 32 had significantly higher EATTi (5.27 ± 0.66 mm/m2) compared to those with lower scores. An EATTi greater than 4.15 mm/m2 predicted more complex CAD (SYNTAX score >22) with 80% sensitivity and 86% specificity. The intra- and interobserver reproducibility for the EATTi measurement were excellent (intra-class correlation coefficient 0.911, inter-class correlation coefficient 0.895). Conclusions: EATTi is significantly associated with CAD complexity in patients undergoing open-heart surgery. It serves as a reliable indicator of more intricate CAD forms, as reflected by higher SYNTAX scores. These findings highlight the clinical relevance of EATTi in pre-operative assessment, suggesting its potential utility as a prognostic marker in cardiac surgical patients.